An introduction to network filters and transmission lines - Chakrabarti, A (Dhanpat Rai & Co (P) Ltd, 2008)
An introduction to network filters and transmission lines / Chakrabarti, A. -- New Delhi: Dhanpat Rai & Co (P) Ltd., 2008 621.3192 C426e3 3rd ed. No. of Copies : 1